Nucleoside Hydrolase NH 36: A Vital Enzyme for the Leishmania Genus in the Development of T-Cell Epitope Cross-Protective Vaccines - Palatnik-de-Sousa, Clarisa Beatriz (Frontiers in Immunology, 2019)
NH36 is a vital enzyme of the DNA metabolism and a specific target for anti-Leishmania chemotherapy. We developed second-generation vaccines composed of the FML complex or its main native antigen, the NH36 nucleoside hydrolase of Leishmania (L.) donovani and saponin, and a DNA vaccine containing the NH36 gene. All these vaccines were effective in prophylaxis and treatment of mice and dog visceral leishmaniasis (VL). The FML-saponin vaccine became the first licensed veterinary vaccine against leishmaniasis (Leishmune®) which reduced the incidence of human and canine VL in endemic areas. The NH36, DNA or recombinant protein vaccines induced a Th1 CD4+IFN-γ+ mediated protection in mice. Efficacy against VL was mediated by a CD4+TNF-α T lymphocyte response against the NH36-F3 domain, while against tegumentary leishmaniasis (TL) a CD8+ T lymphocyte response to F1 was also required. These domains were 36-41 % more protective than NH36, and a recombinant F1F3 chimera was 21% stronger than the domains, promoting a 99.8% reduction of the parasite load. We also identified the most immunogenic NH36 domains and epitopes for PBMC of active human VL, cured or asymptomatic and DTH+ patients. Currently, the NH36 subunit recombinant vaccine is turning into a multi-epitope T cell synthetic vaccine against VL and TL.